User evaluation of the interfaces for the remote control of manufacturing systems - Spasojević-Brkić, Vesna K; Punik, Goran (Serbian Journal of Management, 2013)
Abstract This paper is a contribution to the new direction for enhancement in remote controlling functionality in manufacturing systems and presents a methodology for evaluating user interfaces for the remote control of a Ubiquitous Manufacturing System. Survey is based on the experiment that involved 68 subjects, students at the Faculty of Mechanical Engineering, the University of Belgrade, Serbia, as future users of the interface for the remote collaborative control of manufacturing systems. The results show that the user evaluation instrument consists of usability and collaboration as correlated measures. Usability comprises effectiveness, efficiency and representational fidelity measures, while collaboration includes collaboration effort, awareness/ involvement and co-presence. The results of this survey will help in future design decisions and measuring its quality of use. Keywords: interface, evaluation, remote control, manufacturing system Rezime Rad predstavlja doprinos novom pravcu unapredjenja daljinskog upravljanja funkcionalnostima i prezentuje metodologiju za procenu korisničkih interfejsa za daljinsko upravljanje ubikvitnim proizvodnim sistemima. Istraživanje je zasnovano na eksperimentu, koji je uključio 68 ispitanika, studenata Mašinskog fakulteta Univerziteta u Beogradu, koji predstavljaju buduće korisnike interfejsa za daljinsko kolaborativno upravljanje proizvodnim sistemima. Rezultati pokazuju da se instrument za ocenu sastoji od koreliranih mera korisnosti i kolaboracije. Korisnost sadrži mere efikasnosti, efektivnosti i reprezentativne tačnosti, dok kolaboracija uključuje napor, uključenost i koprisutnost. Rezultati rada treba da pomognu pri odlučivanju u budućem dizajniranju i pri merenju kvaliteta upotrebe. Ključne reči: interfejs, evaluacija, daljinsko upravljanje, proizvodni sistem